2019
DOI: 10.26906/sunz.2019.4.040
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Professional Competence of Future It Specialists in Institutions of Higher Education

Abstract: The paper considers modern information technologies, which are the basis of the process of informatization of education. The process of improving the quality of training specialists in the context of developing a system of general and vocational education is researched. The author analyzes the definition of informational educational environment. It is substantiated that online education is a factor in increasing the level of access to education and has certain advantages over traditional types of knowledge, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…The introduction of the educational environment put an end to the old approaches to the administration of the educational process and stopped the atomization of student groups. The forced nature of the use of IT for the formation of the educational environment and its effectiveness in counteracting the process of atomization of student groups is not mentioned even in a sufficiently thorough work [6,18]. At the same time, the authors of the presented article agree with the main thesis of the paper [6] about the importance of the role of IT and ICT as a tool for implementing the latest approaches in shaping the educational environment.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…The introduction of the educational environment put an end to the old approaches to the administration of the educational process and stopped the atomization of student groups. The forced nature of the use of IT for the formation of the educational environment and its effectiveness in counteracting the process of atomization of student groups is not mentioned even in a sufficiently thorough work [6,18]. At the same time, the authors of the presented article agree with the main thesis of the paper [6] about the importance of the role of IT and ICT as a tool for implementing the latest approaches in shaping the educational environment.…”
Section: Discussionmentioning
confidence: 76%
“…The forced nature of the use of IT for the formation of the educational environment and its effectiveness in counteracting the process of atomization of student groups is not mentioned even in a sufficiently thorough work [6,18]. At the same time, the authors of the presented article agree with the main thesis of the paper [6] about the importance of the role of IT and ICT as a tool for implementing the latest approaches in shaping the educational environment. The set of related consequences is multifaceted and will require further research, which, in particular, is indicated in the work of Tsiuniak [8].…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations